Teachers' Strategies in Increasing Students' Interest in Reading the Qur'an - Jihan; Ummi Hanifaa; Arlina; Gadis Ayuni Putri; Hendra Susilo Saragih (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to analyze the strategies used by teachers to increase students' interest in reading the Koran. The focus of the study is on 3 things, namely what strategies do teachers use to increase interest in reading the Al-Qur'an in students, what strategies do teachers use in increasing interest in reading Al-Qur'an in students and why are these strategies used by teachers in increasing interest in reading Al-Qur'an? -Qur'an. This research analyzes teacher strategies in increasing interest in reading the Al-Qur'an among MTSS Lab IKIP Al-Wasliyah. The research method used is qualitative phenomenology. The data collection techniques used are observation, interviews and documentation. The conclusion that can be drawn from this research is that the teacher's strategy in increasing students' interest in reading the Koran is very important. By implementing the right strategy, it will create a pleasant learning atmosphere so that students will feel interested and not easily bored in learning to read the Al-Qur'an.